A Novel Proposal for an Adapted Vehicle for Informal Waste Pickers in Ambato – Ecuador - Goyes Balladares, Andrea Cristina; Pardo Jara, Ingrid Dennise; Moya Jiménez, Roberto Carlos (INGENIO, 2024)
Solid waste management represents a challenge for contemporary cities because it involves various levels of management and processing. At the base of the recycling pyramid, the crucial role of informal recyclers stands out, whose work improves the environmental conditions of cities. Despite its valuable contribution, informality has marked this profession, with deplorable working conditions at a social and economic level and low occupational safety. Recyclers roam the city in search of as much recyclable material as possible, so they can later sell it and continue the chain. However, the operational process of the recyclers is striking due to the inadequate conditions, in terms of personal protection and mobilization. Traditionally, they move with a cart, a product intended for transporting heavy loads over short distances. However, it is used by waste pickers to travel long distances during the daily working day. Through the methodology of early and continuous validation for product design, a vehicle adapted for the work of informal recyclers in the city of Ambato is proposed. It shows a valuable vision of addressing management in an inclusive, effective way for the city, with adequate working conditions at the operational level for waste pickers.